2017
DOI: 10.1149/2.1411704jes
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Hydrothermal Synthesis of CuS Nanoplate Films on Conductive Substrates as Efficient Counter Electrodes for Liquid-Junction Quantum Dot-Sensitized Solar Cells

Abstract: CuS nanoplate films were synthesized on FTO conducting glass substrates via a facile microwave-assisted hydrothermal (MHT) route and applied directly as a low-cost and high-efficiency counter electrode (CE) for liquid-junction quantum dot-sensitized solar cells (QDSSC). The two-dimensional structure of nanoplate provide high surface area for more active catalytic sites and easy accessibility for polysulfide electrolyte, which leads to the remarkable decrease in charge transfer resistance and the enhancement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Hydrothermal approaches have also been employed for the in situ growth of Co 0.85 Se and Ni 0.85 Se metal selenides on conductive glass substrates to manufacture transparent CEs . Among them microwave‐assisted hydrothermal fabrication of metal sulfide and selenide CEs have been reported which has brought forward enhancement in QDSSCs efficiency at a shorter time and lower cost …”
Section: Introductionmentioning
confidence: 99%
“…Hydrothermal approaches have also been employed for the in situ growth of Co 0.85 Se and Ni 0.85 Se metal selenides on conductive glass substrates to manufacture transparent CEs . Among them microwave‐assisted hydrothermal fabrication of metal sulfide and selenide CEs have been reported which has brought forward enhancement in QDSSCs efficiency at a shorter time and lower cost …”
Section: Introductionmentioning
confidence: 99%
“…Copper sulfate (Cu x S), which is known as a p-type semiconductor, has been utilized for the application of catalysts, 13 solar cells 14–16 and Li ion batteries 17,18 due to its good electrical and optical properties and good physical and chemical stability. 19 The nanoscale morphology of Cu x S expands its potential applications: 20 nanoparticles for bioimaging and photothermal therapy with near-infrared absorption by modulating their size, 21–23 nanosheets or flower-like morphology for Na + ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…19 The nanoscale morphology of Cu x S expands its potential applications: 20 nanoparticles for bioimaging and photothermal therapy with near-infrared absorption by modulating their size, 21–23 nanosheets or flower-like morphology for Na + ion batteries. 24,25 Morphology-controlled growth of Cu x S has been achieved via various techniques, such as sonochemical, 26,27 hydrothermal, 15,28,29 solvothermal 19,30 and CVD methods, 31 to advance the application of Cu x S.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, microwave irradiation method has the advantages of low cost, fast, homogeneous volumetric heating, and facile fabrication. Energy is directly transferred to the precursor solution through an interaction at the molecular level with the electromagnetic field, so-called 'molecular heating', rather than through heat conduction as conventional bathing heating [19][20][21][22]. Therefore, chemical and physical transformations could be promoted.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CEs have a pivotal impact on the photovoltaic performance of QDSSC [7][8][9][10]. An ideal CE requires high electrocatalytic activity, large surface area, favorable electrical conductivity, and low cost [19]. It has been demonstrated that copper selenide has excellent catalytic activity to polysulfide electrolyte that commonly used in QDSSC [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%